Integration into teaching: a pending policy within the framework of a system of lifelong learning in Honduras (Educational Knowledge, 2019)
This article aims to analyze the results of research conducted in 2017 with teachers in the Honduran education system at the primary and secondary levels in both urban and rural areas. The goal is to offer a scientific contribution that will help strengthen a teacher training program for newly qualified teachers as part of their integration into the system.The study focuses on four aspects: the integration of newly qualified teachers, a comprehensive program, ongoing professional development, and teacher identity. Empirical data was collected from active teachers in the departments of Francisco Morazán, Cortés, Atlántida, Choluteca, and Santa Bárbara, located in central, southern, and western Honduras. Technical assistants from the corresponding Departmental Directorates participated in the fieldwork.The study revealed that the Honduran education system has yet to implement an integration program for newly qualified, intermediate, and experienced teachers. This is an educational reality that needs to be discussed and addressed by educational authorities. Furthermore, if possible, an educational policy should be developed in a sound, participatory manner, involving key stakeholders. The current lack of integration programs reflects a weakness in the teaching profession and, consequently, in the competencies within the teaching field; it also reveals a weakness in the understanding of teacher identity and hiring procedures. All of this is reflected in educational quality indicators.In this regard, the study employed qualitative techniques such as collaborative focus groups and interviews as methodological instruments. These techniques yielded data on the characteristics of integration programs, the identity of the teaching profession, hiring procedures, and the implemented training models. Additionally, the grounded theory method was used, drawing on theoretical frameworks and official documents.